Insights on Metal Based Dental Implants and their Interaction with the Surrounding Tissues - Popa, Marcela; D. Hussien, Mohamed.; Cirstea, Alexandra; Grigore, Raluca; Lazar, Veronica; Bezirtzoglou, Eugenia; Carmen Chifiriuc, Mariana; Sakizlian, Monica; Stavropoulou, Elisavet; Bertesteanu, Serban (Current Topics in Medicinal Chemistry, 2015)
At present, the use of dental implants is a very common practice as tooth loss is a frequent problem and can occur as a result of disease or trauma. An implant is usually made of biocompatible materials that do not cause rejection reactions and allow the implant union with the respective bone. To achieve this goal, the implant surface may have different structures and coatings, generally used to increase the adherence of the implant to the bone and to decrease the risk of the periimplantar inflammatory reactions. This review gives some insights of the metal based materials used for dental implants, their limits, improvement strategies as well as the pathophysiology, diagnosis, treatment and prevention of periimplantary diseases.
Keywords: Dental implants alloys